Citrus Black Spot Management Timing Schedule - Megan M. Dewdney; Jamie D. Yates (EDIS, 2010)
PP277, a 2-page illustrated handout by Megan M. Dewdney and Jamie D. Yates, provides a condensed version of citrus black spot management recommendations and application timings for various citrus fungal diseases. Published by the UF Department of Plant Pathology, July 2010.